Everyday Justice in Pre-Confederation Canada: The Ledger of Thomas Burrowes, JP of Kingston Mills - Kaufman, Amy (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada)

(untitled) (The Bibliographical Society of Canada/La Société bibliographique du Canada, 2020)
This essay combines close bibliographical analysis of the 1856–66 ledger of Thomas Burrowes, Justice of the Peace for Kingston Mills in what is now Ontario, with a wide-ranging discussion of what the document can reveal about its owner and about the practice of everyday justice in a small mill town in the years leading up to Canadian Confederation. It considers the effect of reading about law in manuscript versus printed form. It follows the intriguing evidence contained within the ledger to consider its possible uses by subsequent owners after Burrowes’s death, tracing the ledger in its circular journey from Kingston Mills to the Queen’s University Archives in Kingston via Detroit and Indiana.